Beyond the Shore: Reconstructing Islamic Worship Jurisprudence for Fishing Communities Through the Lens of Fiqh Sosial - Sahal Mahfudh; Mohammed Adam Mohammed Abdulali (The Institute of Research and Service Community IPMAFA Pati, 2026)
Fishing communities in Pati, Central Java, demonstrate strong Islamic devotion but encounter a persistent